Tailoring the structural and optical properties of ZnO by doping with Cd. Issue 9 (November 2015) - Rana, N.; Chand, Subhash; Gathania, Arvind K.
Abstract: Cadmium-doped zinc oxide (Zn1− x Cd x O (0≤ x ≤0.03)) samples are synthesized by polymeric precursor method. X-ray diffraction, Fourier transform infrared, Raman and Ultraviolet–visible spectroscopy techniques are used for the characterization of the synthesized samples. The X-ray diffraction study shows that Zn1− x Cd x O nanoparticles have wurtzite structure with a weak secondary phase for higher Cd concentration i.e x =0.03. The Raman study demonstrates the red-shift behavior and broadening of the Raman modes with increasing content of Cd in ZnO. It reflects the structural distortion due to the atomic substitution in the samples. Fourier transform infrared analysis has confirmed the presence of Zn–O stretching mode of vibration in the samples. The Ultraviolet–visible spectroscopy shows that the optical band gap exhibit red-shift behavior with the increasing concentration of Cd. The band gap is found to decreases from 3.17 eV for pure ZnO to 3.05 eV for Cd doping concentration of 0.02 at%.